2013
DOI: 10.1002/jcop.21574
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing to Improve Middle School Students’ Academic Performance: A Replication Study

Abstract: Motivational interviewing (MI) is brief therapy originally designed to motivate adults to change risky or dysfunctional behavior. There is a push to use MI with middle and high school students; however, current research focuses on MI with families or teachers or to support program fidelity. In one of the few randomized studies, Strait et al. (2012) found one MI session produced statistically significant changes in middle school students’ math grades and self‐reported positive academic behavior. This study repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…For example, Strait et al (2012) found that middle school students randomly assigned to one 50-minute school-based MI session with a school psychology trainee experienced significant improvements in their math grades as compared to those in the waitlist control condition. Findings were replicated in a follow-up study that used identical procedures with a different cohort of students (Terry, Smith, Strait, & McQuillin, 2013). Terry et al then examined dosage effects (1 vs. 2 sessions) and found that middle school students who participated in a second session had significantly higher grades in math, science, and history, as compared to improvements in only one subject area among students receiving only one session (Terry, Strait, McQuillin, & Smith, 2014).…”
Section: A New Selective Intervention Based In Motivational Interviewmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Strait et al (2012) found that middle school students randomly assigned to one 50-minute school-based MI session with a school psychology trainee experienced significant improvements in their math grades as compared to those in the waitlist control condition. Findings were replicated in a follow-up study that used identical procedures with a different cohort of students (Terry, Smith, Strait, & McQuillin, 2013). Terry et al then examined dosage effects (1 vs. 2 sessions) and found that middle school students who participated in a second session had significantly higher grades in math, science, and history, as compared to improvements in only one subject area among students receiving only one session (Terry, Strait, McQuillin, & Smith, 2014).…”
Section: A New Selective Intervention Based In Motivational Interviewmentioning
confidence: 97%
“…The MAP intervention is fashioned in line with other promising school-based applications of MI (Snape & Atkinson, 2016, 2017; Strait et al, 2012; Terry et al, 2013) including those utilized with high school students at-risk for dropping out of school (Iachini et al, 2016; Iachini, Lee, DiNovo, Lutz, & Frey, 2018). Based on published literature, MI—though grounded in strong theory—has not been used as a selective intervention with adolescents taking accelerated coursework.…”
Section: Study Purposementioning
confidence: 99%
“…several writers (Frey, Lee, small, seeley, & Feil, 2013;Reinke, Herman, & sprick, 2011;sheldon, 2010;shepard, Herman, Reinke, & Frey, 2014) have outlined use of MI in education. Current research supporting the use of MI in schools includes: school mental health (Frey, Cloud, Lee, small, & seeley, 2011), special education (Manthey, 2011), disengaged primary age children (Atkinson & Cryer, 2015), at risk students (Hadraba, 2011;Kittles & Atkinson, 2009), truancy (Enea & dafinoiu, 2009) and academic performance (strait, smith, McQuillin, & Terry, 2012;Terry, smith, strait, & McQuillin, 2013).…”
Section: In Educationmentioning
confidence: 99%
“…School-based mental health experts have advocated for School-Based Motivational Interviewing (SBMI) to promote students’ academic achievement (Frey et al, 2011; Strait et al, 2012; Terry, Smith, Strait, & McQuillin, 2013). Motivational Interviewing (MI) is a brief counseling style used to enhance an individual’s intrinsic motivation to change (Miller & Rollnick, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence suggests that it is possible to use MI to increase students’ school performance (Strait et al, 2012; Terry et al, 2013). Originally developed in mental health settings to treat individuals diagnosed with substance use disorders, MI has also been used to motivate positive change in a number of behaviors, including dieting (Hollis, Williams, Collins, & Morgan, 2013), medication adherence (Lundahl et al, 2013) and safe sexual behavior (Lundahl, Kunz, Brownell, Tollefson, & Burke, 2010; Lundahl et al, 2013).…”
Section: Introductionmentioning
confidence: 99%